A Critical Perspective on Ecological "Risk" and "Protective" Factors for Youth Suicide in Canada - Hagen, Melissa (Université d'Ottawa | University of Ottawa, 2022)
Suicide is the second leading cause of death in youth aged 15 to 24 years old in Canada and the magnitude of the problem is of growing concern worldwide. Despite the recognition of this phenomenon as the result of the dynamic interplay between individual, psychological, social, cultural, environmental, and many other factors, current trends in the literature are largely centred on individual “risk” factors. Not only does this individualize and pathologize the problem of suicide, but it also fails to take into account contexts of resilience among youth. In the current research, an ecological framework is adopted to critically analyze the “risk” and “protective” factors for youth suicide, examine the interactive and additive processes across factors, and outline the implications of these findings for research, prevention, and intervention initiatives. A deductive thematic analysis was performed on the data presented in the 21 documents that were retained. The results illustrated that at the ontosystem level, mental health problems and prior suicide attempts should not be overlooked; at the microsystem level, social support and the lack thereof are the most relevant factors; at the mesosystem and exosystem levels, further research is warranted; and at the macrosystem level, ideologies and beliefs, socioeconomic status, Indigenous culture, and systems of oppression each play a role in youth suicide in Canada. Also shown is how the many factors interact both within and across the ecological systems of the youth. Finally, several points drawn from the results of the analysis are discussed, their implications for social work research and intervention are underlined, and recommendations for future research are put forth. Keywords: youth, suicide, suicide-related behaviours, risk, resilience, ecological factors, ecological systems theory, Canada